Knowledge and Practices of Family Planning Among Staff Nurses of Liaquat University of Medical and Health Sciences, Jamshoro/Hyderabad- Sindh - Suhail Ahmed Gadhi; Fida Hussain Jakhrani; Mir Ghulam Mustafa Thaheem; Muhammad Ali Abbasi (International Journal of Emerging Multidisciplinaries: Social Science, 2026)
Family planning is an important component of reproductive health and contributes to healthy birth spacing, informed reproductive decision-making, and improved maternal and family well-being. Nurses have an important role in family-planning services because of their direct contact with women, couples, and families and their responsibilities for health education, counselling, referral, and clinical support. This study assessed knowledge and practices of family planning among married staff nurses at Liaquat University of Medical and Health Sciences, Jamshoro/Hyderabad. A descriptive cross-sectional design was used. A structured questionnaire was administered to 100 married staff nurses selected through simple random sampling. The questionnaire covered demographic characteristics, knowledge of family-planning methods, sources of information, communication with spouses, contraceptive practices, access to services, partner support, and barriers to utilization. The findings showed that 98% of respondents knew at least one family-planning method, 91% considered birth spacing important, and 89% could identify at least two modern methods. Health-care providers were the main source of information for 64% of respondents. Forty-seven percent were currently using a family-planning method, while 53% were not currently using any method. Withdrawal, oral pills, injectables, male condoms, IUCDs, and permanent methods were reported among current users. The major reasons for non-use were desire for more children, concern about side effects, social and cultural stigma, partner or family preference, and concerns related to sexual satisfaction. Professional experience was associated with knowledge, while age was associated with practice. The findings indicate that awareness of family planning is high among staff nurses, but important barriers remain between knowledge and sustained practice. Strengthening counselling, confidentiality, follow-up, partner communication, and continuing professional education may improve family-planning service utilization.